Timing of Administration: For Commonly-Prescribed Medicines in Australia - Gagandeep Kaur; Craig L. Phillips; Keith Wong; Andrew J. McLachlan; Bandana Saini (MDPI AG, 2016)
Chronotherapy involves the administration of medication in coordination with the body's circadian rhythms to maximise therapeutic effectiveness and minimise/avoid adverse effects. The aim of this study is to investigate the "time of administration" recommendations on chronotherapy for commonly-prescribed medicines in Australia. This study also aimed to explore the quality of information on the timing of administration presented in drug information sources, such as consumer medicine information (CMI) and approved product information (PI). Databases were searched for original research studies reporting on the impact of "time of administration" of the 30 most commonly-prescribed medicines in Australia for 2014. Further, time of administration recommendations from drug information sources were compared to the evidence from chronotherapy trials. Our search revealed 27 research studies, matching the inclusion and exclusion criteria. In 56% (n = 15) of the research studies, the therapeutic effect of the medicine varied with the time of administration, i.e., supported chronotherapy. For some medicines (e.g., simvastatin), circadian-based optimal administration time was evident in the information sources. Overall, dedicated studies on the timing of administration of medicines are sparse, and more studies are required. As it stands, information provision to consumers and health professionals about the optimal "time" to take medications lags behind emerging evidence.